Vitamin B12 Deficiency in Children Due to Lack of Intake: A Report of Two Cases at the Pediatric Department at Aristide Le Dantec Hospital - Y., Keita; A.A., Ndongo; A., Thiongane; M.N., Sylla; F., Ly; A., Ba; D.I., Ly; B, Niang; A, Sylla (Journal of Pediatric Health And Nutrition, 2021)
We report 2 cases of vitamin B12 deficiency in children due to deficient intake. These were 2 girls aged 4 years (case 1) and 6 years (case 2), respectively, hospitalized in December 2020 and March 2021 in the pediatric ward of Le Dantec hospital. Both patients presented with aregenative anemia, melanoderma and undernutrition. The bone marrow count in case 1 showed a dysmyelopoiesis with megablastosis. The blood vitamin B12 level was low in both cases. Folic acid blood levels were normal in both patients, but an associated martial deficiency was found in case 2. The dietary survey revealed a lack of intake of animal products rich in vitamin B12. Vitamin B12 replacement therapy was effective with rapid regression of all clinical signs observed in both children. The control of the vitamin B12 level after 1 month of treatment was normal in both patients. The disappearance of the symptoms under substitute treatment confirmed the deficiency of Vitamin B12 intake in both patients. Conclusion: Both of our patients had a profound Vitamin B12 deficiency in a context of deficiency in nutrition. The regression of the symptoms was spectacular under vitamin B12 replacement therapy, confirming the deficiency. We recommend in our context a contribution in micronutrients such as vitamins in children after weaning to avoid dietary errors.
Keywords: Vitamin B12; Child; Senegal